Drink that Joe : When is a Good Time for Coffee? - Damitz, Rebekah; Action, Christopher; Schulz, Emily; Peden, Blaine F. (My University, 2018)
Adan, Prat, & Sanchez-Turet (2008) found that decaffeinated coffee affects women more than men. Men experience a larger deficit in sleep quality, than women do, after caffeine consumption before bed than do women. Both genetics and environment play equal roles in likelihood of coffee consumption, suggesting that those surrounded by coffee will drink coffee. In this study, we identify working individuals by those wearing a work uniform, nametag, or professional type clothing (dress slacks, blazers, buttoned/collared shirts/blouses, or a dress). Due to a lack of past research finding what types of people frequent coffee shops, we wanted to provide a preliminary answer to this question.
Color poster with text and graphs.
Keywords: Coffee; Gender differences; Clothing and dress; Posters